VI Simposio Nacional de Estomatología, 2016 - Ricardo Rodríguez Llanes; Dra. Estela de los Angeles Gispert Abreu (Editorial Ciencias Médicas, 2017)
The Cuban Society of Stomatology, under the auspices of the National School of Public Health and the National Direction of Stomatology, held the sixth edition of the National Symposium "Vision Oral Health," in October 2016. In the preparatory framework several activities were developed: The First International Cuba-US Stomatology Meeting, held from September 19 to 21, 2016, at the Panorama Hotel, Havana, Cuba, with slender Cubans and Americans, who presented topics on the Cuban Health System and the Stomatology strategy, the training of human resources in both countries and the presentation of a catalog of US medicines and dental products; the American delegates expressed the willingness to establish links for the development of the profession and the oral health of the population in both countries. The previous purpose was also expressed during a subsequent meeting, in which the Dean of the Cooperative University of Colombia (Bogota headquarters), representatives of the International College of Dentists, the Dean and another colleague and professor of the School of University Dentists participated. de Marquette, together with representatives of the National Council of Scientific Societies of Health, the Executive Committee of the Cuban Society of Stomatology, its scientific body and career leaders from several provinces. Between October 3 and 5, ten presimposio courses were offered in which content was discussed and deepened in order to improve the quality of life of the Cuban population. The II National Encounter of Technicians and Technologists in Stomatology is highlighted. The central activity of the symposium took place at the International Health Center "La Pradera", on October 6 and 7, which was chaired by: Dr.Cs. Pastor Castell Florit Serrat, Director of the National School of Public Health; MSc. Dr. Mariela García Jordán, Head of the National Department of Stomatology; MSc. Dr. Pedro L. Veliz Martínez, Director of the National Council of Scientific Societies of Health; Dr.C. Ileana Grau León, Dean of the Faculty of Stomatology of Havana; MSc. Dr. Mirtha Herrera Nordet, Honorary Member of the Cuban Society of Stomatology; and Dr.C. Estela de los Ángeles Gispert Abreu, President of the Cuban Society of Stomatology. Several lectures were then delivered, "Production of population oral health and intersectoral empowerment" of Dr.C. Estela de los Ángeles Gispert Abreu and Dr.Cs. Pastor Castell-Florit Serrate; "National Stomatology Strategy and its current priorities" of the MSc.Dra. Mariela García Jordán and "Considerations for the improvement of Attention to the Elderly" of Dr.C. Héctor D Bayarre Vea and the MSc. Dr. Jorge Luis Bécquer Águila. In the afternoon lectures, traditional and digital posters were presented, with themes of health promotion, diagnosis and treatment with new technologies for the control of the hypersensitivity, effectiveness and safety of the Biograft-G and the combination of Apafill-G® and calcium hydroxide in bone repair; the latter offered by Dr. Mayra de la Caridad Pérez Álvarez. On the second day, the most relevant dissertations dealt with cancer of the head and neck, including oral cancer, its incidence and educational intervention strategies for its prevention in different population groups; round table offered by professors of the Institute of Oncology and Radiobiology, moderated by the MSc. Dr. Gilda L García Heredia. The scientific works in the form of posters, were characterized by the presentation of educational strategies for the prevention of the most frequent oral diseases in our environment and a proposal of a new model of clinical history for the Primary Care of Stomatological Health of Dr. Miguel Angel Barrio de la Torre (Guantánamo province), which monopolized the largest number of attendees in its presentation.